Pelatihan Penggunaan Microsoft Office Bagi Siswa SMPS St. Yosef Maubesi - Yosep PK. Kelen; Yasinta OL Rema; Renaldi Y. Kolloh; Valerianus Naat; Elsa M. Benolon; Stefania Y. Nule (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2020)
The use of learning media by students, one of which is Microsoft Office, is an ability and skill that must be possessed in the era of globalization and also in the implementation of online learning. Through community service activities (PkM) we provide training to students of SMPS St. Yosef Maubesi as a solution to their low ability to use Microsoft Office, especially Microsoft office Word, Excel and Powerpoint. The training, which is carried out in three stages and includes providing modules or teaching materials, is able to increase the confidence and ability of students in using Microsoft Office. The output is in the form of modules or teaching materials for using Microsoft Office.